Biogeochemical Anomalies at Two Southern California Current System Moorings During the 2014–2016 Warm Anomaly‐El Niño Sequence. Issue 10 (16th October 2019) - Lilly, Laura E.; Send, Uwe; Lankhorst, Matthias; Martz, Todd R.; Feely, Richard A.; Sutton, Adrienne J.; Ohman, Mark D.
Abstract: We analyzed impacts of the 2014–2015 Pacific Warm Anomaly and 2015–2016 El Niño on physical and biogeochemical variables at two southern California Current System moorings (CCE2, nearshore upwelling off Point Conception; CCE1, offshore California Current). Nitrate and Chl‐ a fluorescence were <1 μM and <1 Standardized Fluorescence Unit, respectively, at CCE2 for the entire durations of the Warm Anomaly and El Niño, the two longest periods of such low values in our time series. Negative nitrate and Chl‐ a anomalies at CCE2 were interrupted briefly by upwelling conditions in spring 2015. Near‐surface temperature anomalies appeared simultaneously at both moorings in spring 2014, indicating region‐wide onset of Warm Anomaly temperatures, although sustained negative nitrate and Chl‐ a anomalies only occurred offshore at CCE1 during El Niño (summer 2015 to spring 2016). Warm Anomaly temperature changes were expressed more strongly in near‐surface (<40 m) than subsurface (75 m) waters at both moorings, while El Niño produced comparable temperature anomalies at near‐surface and subsurface depths. Nearshore Ωaragonite at 76 m showed notably fewer undersaturation events during both warm periods, suggesting an environment more conducive to calcifying organisms. Planktonic calcifying molluscs (pteropods and heteropods) increased markedly in springs 2014 and 2016 and remained modestly elevated in spring 2015. Moorings provide high‐frequency measurements essential for resolving the onset timing of anomalous conditions and frequency and duration of short‐term (days‐to‐weeks) perturbations (reduced nitrate and aragonite undersaturation events) that can affect marine organisms. Plain Language Summary: The 2014–2016 Pacific Warm Anomaly‐El Niño sequence significantly changed ocean conditions in the California Current System, but impacts of these anomalies on nutrients, chlorophyll‐ a, and pH, and comparisons to past El Niño events, have not been well described. We examined 9 years (2010–2018) of data from two ocean moorings that provide hourly measurements at fixed locations in the southern California Current System, allowing us to determine both subseasonal and multiyear ecosystem changes. We found that nitrate (important for primary production) and chlorophyll‐ a were anomalously low in nearshore waters throughout the Warm Anomaly and El Niño, suggesting nutrient delivery to the surface ocean was reduced. The Warm Anomaly and El Niño both produced anomalously warm shallow temperatures, but only El Niño produced significantly warmer waters below 50‐m depth. Aragonite, a carbonate mineral important for shell production in calcifying marine organisms, showed elevated saturation state during both the Warm Anomaly and El Niño, suggesting the two anomalous periods produced favorable calcification conditions. Planktonic shelled molluscs, a key component of the oceanic food web, increased during both the Warm Anomaly and El Niño. Our findings may help predict impacts of future anomalies on nutrient availability and biological responses in the California Current System. Key Points: Nearshore nitrate and Chl‐ a fluorescence were near zero for most of the Warm Anomaly‐El Niño but increased briefly in spring 2015 Temperature increases were surface‐intensified across the region during the Warm Anomaly, while El Niño also affected subsurface waters Planktonic mollusc biomass was elevated in springs 2014 and 2016 in conjunction with Warm Anomaly and El Niño aragonite supersaturation